Robot-assisted thoracic surgery versus video-assisted thoracic surgery for lung lobectomy or segmentectomy in patients with non-small cell lung cancer: a meta-analysis - Ma, Jianglei; Li, Xiaoyao; Zhao, Shifu; Wang, Jiawei; Zhang, Wujia; Sun, Guangyuan (BMC cancer, 2021)
It remains no clear conclusion about which is better between robot-assisted thoracic surgery (RATS) and video-assisted thoracic surgery (VATS) for the treatment of patients with non-small cell lung cancer (NSCLC). Therefore, this meta-analysis aimed to compare the short-term and long-term efficacy between RATS and VATS for NSCLC. Pubmed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Medline, and Web of Science databases were comprehensively searched for studies published before December 2020. The quality of the articles was evaluated using the Newcastle-Ottawa Scale (NOS) and the data analyzed using the Review Manager 5.3 software. Fixed or random effect models were applied according to heterogeneity. Subgroup analysis and sensitivity analysis were conducted. A total of 18 studies including 11,247 patients were included in the meta-analyses, of which 5114 patients were in the RATS group and 6133 in the VATS group. Compared with VATS, RATS was associated with less blood loss (WMD = - 50.40, 95% CI -90.32 ~ - 10.48, P = 0.010), lower conversion rate (OR = 0.50, 95% CI 0.43 ~ 0.60, P < 0.001), more harvested lymph nodes (WMD = 1.72, 95% CI 0.63 ~ 2.81, P = 0.002) and stations (WMD = 0.51, 95% CI 0.15 ~ 0.86, P = 0.005), shorter duration of postoperative chest tube drainage (WMD = - 0.61, 95% CI -0.78 ~ - 0.44, P < 0.001) and hospital stay (WMD = - 1.12, 95% CI -1.58 ~ - 0.66, P < 0.001), lower overall complication rate (OR = 0.90, 95% CI 0.83 ~ 0.99, P = 0.020), lower recurrence rate (OR = 0.51, 95% CI 0.36 ~ 0.72, P < 0.001), and higher cost (WMD = 3909.87 USD, 95% CI 3706.90 ~ 4112.84, P < 0.001). There was no significant difference between RATS and VATS in operative time, mortality, overall survival (OS), and disease-free survival (DFS). Sensitivity analysis showed that no significant differences were found between the two techniques in conversion rate, number of harvested lymph nodes and stations, and overall complication. The results revealed that RATS is a feasible and safe technique compared with VATS in terms of short-term and long-term outcomes. Moreover, more randomized controlled trials comparing the two techniques with rigorous study designs are still essential to evaluate the value of robotic surgery for NSCLC.